The El Niño phenomenon under a geological conception - Campoblanco Díaz, Honorio (1999)
The El Niño phenomenon is a natural event, frequent in the fire belt of the Pacific Ocean, characterized by intense tectonic activity: volcanic and seismic that add energy to the ocean floor and the atmosphere causing the El Niño tectonic phenomenon. The Earth is made up of geospheres to the solid, crystalline, liquid and gaseous states arranged according to their density. They all rotate east at different speeds. The solid and crystalline geospheres of the central core and the outer lithosphere rotate faster than the fluid geospheres of the interior and exterior, generating an increasing differential space (D x) that increases from East to West and governs the movement of the trade winds. and cold sea currents. The instant when D x = 0 there will be a superposition of geospheres at the South American level, with cancellation of the trade winds and cold marine currents, generating the tectonic El Niño in these latitudes, meanwhile at 180 ° of it La Niña will manifest. The superposition of geospheres in other latitudes of the Pacific Ocean also generates tectonic El Niño, however, these phenomena are very weak, dominated by the opposite effects to warming, since the oceanic or continental crust at said latitudes is thicker and less fractured , not allowing the easy exit of magma and energy to the ocean floor and continental crust, therefore dominating La Niña stages. At the moment of superposition, tectonism is invigorated with sulfur-laden earthquakes and volcanisms that react with oxygen in the air or oceans to form SO2 and SO3, which upon contact with water become sulfuric acid (H2SO4), these reactions Thermochemicals cause the consumption of oxygen in the environment, heating and acidification of the air and the ocean, causing the breakdown of the trophic chain due to the reduction of nutrients with the consequent death and disappearance of marine and terrestrial species. In the case of subaerial volcanisms saturated with ash and sulfur, the temperature, density and viscosity of the atmosphere increase, making the air denser and more erosive, attacking the epithelial tissues of living beings in contact with the fluid, causing respiratory infections (asthmatics, bronchial) and cases of conjunctivitis among others. During tectonic El Niño phenomena, volcanoes add different chemical elements and isotopes to the environment such as: HCl, F, Br, CO, CO2, N, H, Ca, Ba, Cd, S, H2S, CH4, Mn. etc. that in contact with oxygen and water produce subsequent chemical and thermochemical reactions, consuming oxygen from the medium. These elements present in the environment are assimilated by the different organisms, algae, corals, mollusks, etc. and in the isotopic studies carried out in these species, a large part of them are present. For their part, Dumbar, Wellington, Colgan and Glynn report a decrease in the content of O (18) isotopes in the structure of the Galapagos corals during events. de El Niño, supporting what is proposed in this thesis. These acidic and hot waters, product of the thermal and thermochemical reactions of submarine sulphurous volcanisms, in their movement through the ocean depths, attack the coral reef colonies, causing their discoloration, weakening, which after years or decades will produce extinction and death. of said species. The ENSO event from 1982-1983 killed almost all the corals in the Galapagos and other latitudes of the eastern Pacific Ocean (4).